The Effects of Musical Fit on Choice Between Competing Pairs of Cultural Products - Yeoh, J.; North, Adrian (Ohio State University * School of Music, 2009)
Previous studies have claimed that music can prime the selection of certain products and influence consumers’ propensity to spend because it activates related knowledge of the world and subsequently raises the salience of certain products and behaviors associated with that music. Music that corresponds with the attributes of certain products therefore can prime the selection of those products. Ethnically Chinese Malaysian participants were presented with six pairs of products, each containing a Malay or an Indian version of the product in question, and asked to state a preference for one from that pair. Malay or Indian music was played simultaneously in the background. Product choices corresponded with the ethnicity of the background music played. This demonstrates that music ‘fit’ can influence product choice when consumers do not have a clear existing preference for one product over another.